Weeding as a Sustainable Practice: Ethical Implications for Library Collection Management - Y. Hormiyo; K.L. Mahawar (International Journal of Trends in Humanities, 2026)
Libraries continually refine their collections to ensure they remain relevant, reliable, and representative of their users' needs. However, the process of weeding raises pressing ethical and environmental concerns. This study reframes weeding as a practice of ethical stewardship and sustainable collection management rather than a routine technical procedure. It introduces the Ethical-Sustainability Weeding Framework (ESWF), a conceptual model integrating ethical responsibility, Institutional transparency, and ecological accountability. The ESWF encompasses five interrelated dimensions: policy development, sustainable disposal alternatives, ethical safeguards, and documentation and review. Together, these dimensions guide libraries towards systematic, transparent, and environmentally conscious deselection practices. By emphasizing recycling, donation, and digital preservation, the framework promotes circular use of resources and mitigates environmental impact. The study argues that embedding ethical and sustainable principles into weeding not only optimizes library resources but also reinforces libraries’ social responsibility, ecological commitment, and long-term collection integrity.
Keywords: Sustainability; collection management; deselection; ethics; library collection management; weeding